Bahasa Inggris - Fitria Dwi Wulandari; Rais Sani Muharrami (ITB AAS INDONESIA Surakarta, 2026)
This study examines the influence of the credit ratio (NPF), liquidity ratio (FDR), and capital adequacy ratio (CAR) on the distribution of green financing among Islamic commercial banks in Indonesia during 2021–2024. This research is motivated by the increasing emphasis on sustainable finance and the strategic role of Islamic banking in supporting green economic development. Using a quantitative approach, panel data regression analysis was conducted with EViews 13 on a sample of 9 Islamic commercial banks selected from a population of 14 banks. The results indicate that NPF, FDR, and CAR do not have a significant effect on green credit, suggesting that the distribution of green financing in Islamic commercial banks is not yet driven by internal financial performance. These findings imply that Islamic bank management needs to integrate sustainability considerations more systematically into financing policies, as conventional financial ratios have not been effective in encouraging greater green financing.